Analysis Of The Marketing Distribution Pole Of Tempe Tofu In Lambusa Village Kecamatan Konda South Konawe District: Case Study of Tempet Benjo Tofu Farmers in Lambusa Village - Pika Apriliana R; Abdi, Abdi; Munirwan, Munirwan (International journal of technology and education research, 2024)
This research aims to determine the marketing distribution and analyze the efficiency of tofu and tempe marketing in IRT Benjo, Lambusa Village, Konda District, South Konawe Regency. The research was conducted in Lambusa Village, Konda District, South Konawe Regency, specifically at the Tofu and Tempe Household Industry Benjo. The research took place from October to November 2023. The population in this study consisted of the owners of the Benjo tofu and tempe business, collecting traders, retail traders, and distributor agents whose numbers were unknown. The sample determination technique for marketing institutions was determined using snowball sampling. The total sample size in this study was 17 people, consisting of 1 business owner, 6 retail traders, 5 collecting traders, and 5 distributor agents. The distribution pattern of tofu and tempe marketing was analyzed qualitatively through in-depth interviews with company owners and marketing institutions involved in the product flow from producers to end consumers. The efficiency of tofu and tempe marketing was analyzed using farmer share analysis by dividing the marketing margin at each marketing channel involved with the retail price at the marketing institution level. The results showed that 1) there were two distribution channels involved in the marketing of Benjo tofu and tempe in Lambusa Village, namely distribution channel I, where the Benjo tofu and tempe industry as the producer sold its products directly to end consumers without intermediary marketing institutions, and distribution channel II, where the producer sold its tofu and tempe products through collecting traders, who then resold them to retail traders, who in turn sold them to agents collaborating with kiosks and directly to end consumers, and 2) the marketing efficiency of Benjo tofu and tempe business in Lambusa Village on channel I was 80.48%, and on channel II was 55.61% for collecting traders and 57.78% for retail traders. Thus, it can be said that both the producer and marketing institutions have an efficient marketing system